Copula Density Estimation Using Multiwavelets Based on the Multiresolution Analysis. Issue 9 (20th October 2016) - Chatrabgoun, O.; Parham, G.
Abstract : Recently, wavelet has been used for copula density estimation. A known characteristic of wavelet functions is that they cannot be symmetric, orthogonal, and compact support at the same time while multiwavelets overcome this disadvantage. This article highlights the usefulness of the multiwavelet in order to approximate copula density functions. Possessing three appropriate properties at the same time, high smoothness, and high approximation order properties, multiwavelet can be more precise in copula density approximation. We make this approximation method more accurate by using multiresolution analysis. Finally, we apply our proposed method to approximate the copula density in actuarial data.